Estudo dos efeitos dos agrotóxicos procloraz e piriproxifem sobre o desenvolvimento de Megaleporinus macrocephalus (Anostomidae: Characiformes) - Nardelli, Aline (2019)
Xenobiotics are chemical compounds foreign to the organism, found in an unnatural way. Pesticides are examples of xenobiotics, and used in agriculture for the control of pests and vectors of diseases. These compounds form a very diverse group of chemicals that have different modes of action like endocrine disruptors. Prochloraz is a widely studied compound with effects on non-target organisms in a nonspecific way, which may affect reproduction, development and survival rate. Pyriproxifem, for its part, has few studies, but has already demonstrated a broad spectrum of effects, even at reduced doses, leading to increased mortality, malformations, and interacting with other compounds. Thus, there is a concern that these compounds reach to the aquatic environment affecting anamniotes, which have their life cycle associated with these places. The objective of this work was to evaluate the effects of prochloraz and pyriproxyfen, either alone or in combination, on the larval development of Megaleporinus macrocephalus, a gonocoric species with ZZ / ZW sexual system. Male individuals with the presence of testicular ovarian follicules were obseved in the prochloraz group. The group treated with pyriproxyfen had intersex individuals with reversion from female to male, coinciding with the group of individuals exposed to the mixture of the two compounds. In the pyriproxyfen and combination treatments, spinal bone malformations were observed, with the presence of kyphosis, scoliosis, and malformations in the caudal, pectoral and pelvic fins, the latter with the presence of only a limb bud. These data point to the need for further studies of the compound pyriproxyfen, since it was unspecific and with effects at very small doses in both reproductive and teratogenic aspects.